Dissociable contribution of plasma NfL and p-tau181 to cognitive impairment in Parkinson's disease. (December 2022) - Pagonabarraga, Javier; Pérez-González, Rocío; Bejr-kasem, Helena; Marín-Lahoz, Juan; Horta-Barba, Andrea; Martinez-Horta, Saul; Aracil-Bolaños, Ignacio; Sampedro, Frederic; Campolongo, Antonia; Rivas, Elisa; Puig-Davi, Arnau; Ruiz-Barrios, I.; et al.
Abstract: Background: Cognitive dysfunction is a disabling complication in Parkinson's disease (PD). Accuracy of diagnosis of mild cognitive impairment in PD (PD-MCI) depends on the tests performed, which limits results generalization. Blood-based biomarkers could provide additional objective information for PD-MCI diagnosis and progression. Blood neurofilament light chain (NfL), a marker of neuronal injury, has shown good performance for PD disease stratification and progression. While NfL is not disease-specific, phosphorylated-tau at threonine-181 (p-tau181) in blood is a highly specific marker of concomitant brain amyloid-β and tau pathology. Methods: We investigated the potential of plasma NfL and p-tau181 levels as markers of cognitive impairment in a prospective cohort of 109 PD patients with and without PD-MCI (age 68.1 ± 7 years, education 12.2 ± 5 years), and 40 comparable healthy controls. After a follow-up of 4 years, we evaluated their predictive value for progression to dementia. Results: Although NfL and p-tau181 levels were significantly increased in PD compared with healthy controls, only NfL levels were significantly higher in PD-MCI compared with PD with normal cognition (PD-NC) at baseline. After a follow-up of 4 years, only NfL predicted progression to dementia (HR 1.23, 95% CI 1.02–1.53; p = 0.038). Significant correlations between fluid biomarkers and neuropsychological examination were only found with NfL levels. Conclusions: Plasma NfL levels objectively differentiates PD-MCI from PD-NC patients, and may serve as a plasma biomarker for predicting progression to dementia in PD. Plasma levels of p-tau181 does not seem to help in differentiating PD-MCI or to predict future cognitive deterioration.